The Influence Of Lifestyle And Brand Image On The Purchase Decisions Of Apple Mobile Phone of Sam Ratulangi University Student’s Manado - Maria S. Y Garera; Ferdinand J. Tumewu (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
In the ever-evolving digital era, mobile phones have become a primary need for many individuals, especially premium phones such as Apple that have a significant market share. This study aims to analyze the effect of lifestyle and brand image on purchasing decisions for Apple mobile phones. for students at Sam Ratulangi University, Manado. This study uses quantitative methods with purposive sampling techniques and a survey approach to collect data from a number of respondents who are users or potential users of Apple products. Data analysis was carried out using multiple linear regression to identify the effect of independent variables, namely lifestyle and brand image, on the dependent variable, namely purchasing decisions. with the sample calculation formula used, namely Lemmeshow calculation with a total of 100, then the data was distributed via questionnaire and processed from the SPSS application. The results showed that the two independent variables had a partial and simultaneous influence on purchasing decisions for Apple cellphones. A modern and dynamic lifestyle and a strong and exclusive brand image are proven to be the main factors that encourage consumers to choose Apple products